Auchmerina (Hemiptera: Psylloidea), a psyllid genus in Brazil, associated with Inga spp. (Fabaceae) - Dalva Luiz de Queiroz (Embrapa Florestas, 2021)
Distributional records in Brazil are provided for two psyllid species, Auchmerina limbatipennis Enderlein, documented for the states of Paraná, Rio de Janeiro, Santa Catarina and São Paulo, and A. tuthilli Klimaszewski, for Paraná and Santa Catarina. Host plants for these species are reported for the first time. A. limbatipennis develops on Inga laurina and I. marginata (Fabaceae), and it displays a dimorphism (presence or absence of a distal dark band on the forewing), that is not sexual nor seasonal. A.tuthilli probably develops on Inga spp. As well. For the first time, the immatures of Auchmerina are described.